(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
A new aphid has been collected on Cupressus arizanica in the South of France in 1999 and caught in a 12.2 m suction trap at Pozzuolo del Friuli (Udine province), Northern Italy, since the same year. Some identification characters of the species are illustrated, and elements concerning its biology and natural enemies are discussed.